2020
DOI: 10.1097/md.0000000000021934
|View full text |Cite
|
Sign up to set email alerts
|

Development of central retinal artery occlusion accompanied by choroidal folds in a patient with antineutrophil cytoplasmic antibody-associated vasculitis

Abstract: Rationale: We report a case of central retinal artery occlusion (CRAO) accompanied by choroidal folds in a patient positive for myeloperoxidase (MPO)-antineutrophil cytoplasmic antibody (ANCA). Patient concerns: The study involved a 67-year-old female patient who presented at the Department of Ophthalmology, Osaka Medical College, Takatsuki-City, Osaka, Japan on October 24, 2016 after becoming aware of a sudden decrease of visual acuity (VA) in her right eye. Other than… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…During our literature review, we found several reported cases citing CRAO as the presenting symptom in patients with small vessel vasculitis, including eosinophilic GPA (9) and GPA (10).…”
Section: Discussionmentioning
confidence: 99%
“…During our literature review, we found several reported cases citing CRAO as the presenting symptom in patients with small vessel vasculitis, including eosinophilic GPA (9) and GPA (10).…”
Section: Discussionmentioning
confidence: 99%
“…BVAS is a comprehensive multisystem clinical assessment in AAV and includes eyes in terms of scleritis/episcleritis, conjunctivitis/blepharitis/keratitis, and uveitis. Also, retinal changes are analyzed in BVAS as vasculitis, thrombosis, exudate, hemorrhages: however, all these abnormalities in pre-symptomatic phases can be undiagnosed and, thus, can lead to subclinical chronic damages, at the same time [ 22 , 25 , 26 ]. In accordance with our findings, the OCT-A can be considered as a key diagnostic tool in the early detection of possible subclinical retinal changes in AAV by adding information on disease-damage and activity in pre-symptomatic patients.…”
Section: Discussionmentioning
confidence: 99%
“…BVAS is a comprehensive multisystem clinical assessment in AAV and includes eyes in terms of scleritis/episcleritis, conjunctivitis/blepharitis/keratitis, and uveitis. Also, retinal changes are analyzed in BVAS as vasculitis, thrombosis, exudate, hemorrhages: however, all these abnormalities in pre-symptomatic phases can be undiagnosed and, thus, can lead to subclinical chronic damages, at the same time [22,[25][26]. In accordance with our ndings, the OCT-A can be considered as a key diagnostic tool in the early detection of possible subclinical retinal changes in AAV by adding information on disease-damage and activity in pre-symptomatic patients.…”
Section: Discussionmentioning
confidence: 99%
“…Posterior segment is less commonly involved in AAV, and abnormalities in retinal vessels and/or choroidal circulation have been rarely documented [14][15]. Only few case reports documented occlusive vasculitides in retinal network, particularly in ANCA negative AAV patients [16][17][18][19][20][21][22][23][24][25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%